Poučevanje košarkarskih vsebin v osnovnošolskem in gimnazijskem programu v času povečane možnosti za okužbo z virusom COVID-19 - Sirnik, Matic (Šport (Ljubljana), 2021)
By playing basketball, pupils and students develop a great number of motor abilities, learn complex thinking, and control the space as well as players' and ball's movements, learning about fair play, following the rules and building on their social skills and collaborative relations. Due to all the positive influences of carefully selected and organised basketball content, the latter was included in the primary and secondary school curricula. As protecting our health is of the utmost importance at the present time and knowing that appropriately organised sport activity has positive effects on a person's health as well as physical and motor development, we prepared some recommendations for the selection of basketball content for each training unit, along with advice on how to exercise safely during the COVID-19 epidemic. We also added concrete examples of four practice sessions with basketball content for primary schools and grammar schools.
Keywords: basketball; COVID-19; dijaki; epidemic; epidemije; korona virus; košarka; pupils; students; šport; učenci